If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -3x + 54 = 0 Reorder the terms: 54 + -2x + -3x = 0 Combine like terms: -2x + -3x = -5x 54 + -5x = 0 Solving 54 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + -5x = 0 + -54 Combine like terms: 54 + -54 = 0 0 + -5x = 0 + -54 -5x = 0 + -54 Combine like terms: 0 + -54 = -54 -5x = -54 Divide each side by '-5'. x = 10.8 Simplifying x = 10.8
| -3+7k=1+8k | | Cos(x)+7x=0 | | 100x^2-x-10=0 | | 54=89-36y | | m+599.01=686.98 | | -12c^2-38c=-40 | | c-19.2=24.0 | | 11-8n=1-6n | | 7x+3x=77 | | a-108.8=-203.0 | | r^2+3-2=0 | | x^2+nx+3x+3n=0 | | 2x^2-3-5=0 | | m+19.32=23.86 | | x=3(13/12-4) | | 8x+2=7(x-3)+4 | | x^2-dx-cx+dc=0 | | -6+m=-3m+6m | | 2p-6=-12+8p | | 3-6v+6v=15+3v | | 30+4x=6x-35 | | 9x*-12x+4=0 | | -1(x-6)=8x-12 | | 8p-28=-22+9p | | 1000000+1=x | | 32x+8y=5600 | | 5(2m-5)=7-(m+3) | | -5a+6a=-10+3a | | 432=x(x-6)(x-6) | | -5p+8+6p=10 | | x+3x=4x | | .5x-1.5=-6.5 |